Perbedaan Produksi Susu dan Tingkat Mastitis pada Puting Depan dan Puting Belakang Sapi Perah PFH di KUD Sumbermakmur Kecamatan Ngantang Kabupaten Malang - Salsabila Maula Hanggara; Puguh Surjowardojo (Jurnal Sains Peternakan, 2022)
The purpose of this study was to determine the difference in milk production between the front and rear teat and mastitis in FHC dairy cows in the Ngantang district. The research material was 45 FHC dairy cows with 2nd, 3rd and 4th lactation periods. The method that used was a case study by observing and collecting data at the farm by purposive sampling. The data obtained were analyzed by paired t-test. The results showed that the difference in front and rear teat milk production in FHC dairy cows in the Ngantang district was different. Front teat milk production has an average of 7.31 ± 2.71 kg/cow/day while rear teat milk production has an average of 8.91 ± 2.29 kg/cow/day. There was also a very significant difference in the mastitis score, the average mastitis score of front teat was 0.80 ± 0.92 and the mastitis score to the rear teat was 1.29 ± 1.34. Of the 180 teat tested for mastitis, there were 68 teat that were positive for subclinical mastitis, the average being the rear teat because the milk production was higher than the front teat. These results indicate that the front and rear teatmilk production is highly significant (P < 0.01).